2005
DOI: 10.1007/s11104-005-0874-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between plant and soil water status in vine (Vitis vinifera L.)

Abstract: Soil water status and its effect on plant water status are commonly evaluated for water stress diagnosis in annual crops. We investigated the application of this method to vineyards, using the fraction of transpirable soil water (FTSW) to characterise the soil water deficit experienced by the plant. The stability of the relationship between FTSW and predawn leaf water potential ( p) was analysed over two years (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 20 publications
3
77
1
Order By: Relevance
“…mid-June to mid-September, 28 dates) by TDR (TRIME-T3 IMKO GmbH, Ettlingen, Germany; precision ±2 %). From SW measurements FTSW data were computed as defined in the work by Pellegrino et al (2005b). The minimum and maximum SW values necessary to compute the FTSW were found with a complete search over all available measurements for each depth.…”
Section: Ftsw Measurement and Spatialisationmentioning
confidence: 99%
“…mid-June to mid-September, 28 dates) by TDR (TRIME-T3 IMKO GmbH, Ettlingen, Germany; precision ±2 %). From SW measurements FTSW data were computed as defined in the work by Pellegrino et al (2005b). The minimum and maximum SW values necessary to compute the FTSW were found with a complete search over all available measurements for each depth.…”
Section: Ftsw Measurement and Spatialisationmentioning
confidence: 99%
“…For these types of artificial forests, the spatiotemporal variation of the soil water is very pronounced [3] because of antecedent precipitation, surface runoff, surface evaporation, transpiration, soil characteristics, plant root absorption, and so on [4,5]. Some studies have suggested that soil water plays a key role in plant growth [6,7], and it is likely to be a limiting factor for plant growth on the semiarid Loess Plateau, China [8]. Therefore, the effects of artificial forest construction on soil water dynamics are very important when implementing vegetation restoration projects in this area [9].…”
Section: Introductionmentioning
confidence: 99%
“…Soil and plant assessments were similar in the two experiments. Soil water content was monitored with a neutron probe (Évora) or a capacitance probe (Reguengos) in 4 access tubes per treatment installed in the row between two contiguous vines with readings taken periodically at increments of 0.2 m (Évora) or 0.1 m (Reguengos) from soil surface to a depth of ca 1.0 m. The fraction of transpirable soil water was calculated according to [22]. Predawn and midday leaf water potential were measured in fully mature and well-exposed leaves per treatment, on the day before irrigation, using a pressure chamber.…”
Section: Methodsmentioning
confidence: 99%